The Influence of Work Motivation and Organizational Culture on Employee Performance at PT. Srikandi Inti Lestari in Surabaya - Ika Sari; Rifki Suwaji (Jurnal Informasi dan Teknologi, 2024)
Work motivation is a crucial element within a company as it enhances employee morale and performance. Organizational culture also serves as a guiding principle for employees in fulfilling their responsibilities and adhering to behavioral values. This study aims to analyze the partial influence of work motivation and organizational culture on employee performance at PT. Srikandi Inti Lestari in Surabaya. The research population comprises all 85 employees of PT. Srikandi Inti Lestari, all of whom participated as respondents. Data analysis methods included descriptive percentage analysis and multiple linear regression, with partial (t-test) and coefficient of determination tests. The results from the linear regression analysis technique indicate that work motivation and organizational culture significantly influence employee performance at PT. Srikandi Inti Lestari in Surabaya (Y = -6.707 + 0.530X1 + 0.349X2, t = 6.228, p = 0.000). It is expected that the company can maintain and enhance attention to employee needs, as well as provide support and encouragement to improve employee performance.